2004
DOI: 10.1016/j.jasms.2004.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Collisional activation of ions in RF ion traps and ion guides: The effective ion temperature treatment

Abstract: Ion transfer and storage using inhomogeneous radio frequency (RF) electric fields in combination with gas-assisted ion cooling and focusing constitutes one of the basic techniques in mass spectrometry today. The RF motion of ions in the bath gas environment involves a large number of ion-neutral collisions that leads to the internal activation of ions and their effective "heating" (when a thermal distribution of internal energies results). The degree of ion activation required in various applications may range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 47 publications
(63 reference statements)
4
72
0
Order By: Relevance
“…It has been demonstrated that for low Q values (such as 0.25, used for these experiments) the effective temperature of ions held at zero collision energy inside an ion trap is approximately equivalent to the temperature of the buffer gas, and hence the temperature of the gas inlet to the trap itself. 31,32 Gronert has determined the effective temperature of ions contained within a three dimensional ion trap (from the same manufacturer as the linear trap employed herein) to be 310±20 K, by measurement of the equilibrium constant of a complexation reaction displaying very large temperature dependence. 32 Collision rates z have been calculated at 307 K by average dipole orientation (ADO) theory 33 using an available Fortran routine 34 to enable reaction efficiencies to be estimated.…”
Section: Reactions Of the Bridgehead Radicalmentioning
confidence: 99%
“…It has been demonstrated that for low Q values (such as 0.25, used for these experiments) the effective temperature of ions held at zero collision energy inside an ion trap is approximately equivalent to the temperature of the buffer gas, and hence the temperature of the gas inlet to the trap itself. 31,32 Gronert has determined the effective temperature of ions contained within a three dimensional ion trap (from the same manufacturer as the linear trap employed herein) to be 310±20 K, by measurement of the equilibrium constant of a complexation reaction displaying very large temperature dependence. 32 Collision rates z have been calculated at 307 K by average dipole orientation (ADO) theory 33 using an available Fortran routine 34 to enable reaction efficiencies to be estimated.…”
Section: Reactions Of the Bridgehead Radicalmentioning
confidence: 99%
“…The internal energy of ions in the trap can be characterized by a Boltzmann distribution and effective ion temperature [31]. Here the following equation was used to calculate the effective temperature [31]:…”
Section: Numerical Simulationmentioning
confidence: 99%
“…Typically, a sample is ionized via nano-ESI and then the metering valves are opened to introduce the reagent vapors as desired. In some cases, the charge states were difficult to resolve due to the presence of adducts (e.g., attached acid or base molecules), but these were easily removed using dipolar DC collision-induced dissociation (DDC-CID), a broad-band collisional activation technique [47][48][49].…”
Section: Apparatus and Proceduresmentioning
confidence: 99%
“…When HCl vapors were introduced into the interface, higher charge state distributions (+27 to +14) of both apo-and holo-myoglobin were observed, as well as a third distribution at the +8 to +9 charge states that corresponded to myoglobin with two heme groups (Figure 8b). DDC CID [47][48][49] was used to clean-up the spectra in order to better determine the identity of the latter distribution. The observation of the three distinct myoglobin distributions (viz., apo-, holo-, and two heme versions) from a solution of holo-myoglobin prepared at basic pH, ionized in the positive mode, and exposed to acid vapors might be rationalized in several ways.…”
Section: Proteins With Noncovalently-bound Co-factorsmentioning
confidence: 99%